Natural Antibacterial and its Use. Issue 1 (April 2021) - Nendissa, Sandriana J; Mahendradatta, Meta; Zainal,; Bastian, Februadi
Abstract: In today's era, the use of natural antimicrobials such as plant extracts to preserve food processed products has received much attention from researchers. This is related to the increasing public awareness of synthetic chemical preservatives. Various types of plants have been stated to produce extracts that are effective in inhibiting the growth of bacteria that destroy food processed products, such as atung seed ethyl acetate extract ( Parinarium glaberrimum Hassk ) Bacillus cereus, Bacillus subtilis, Staphylococcus aereus, while pathogenic bacteria are Escherechia coli, Salmonella enternidi s; Guava leaf extract has a high tannin compound capable of suppressing the development of Aeromonas hydrophila bacteria in Gurame fish ( Osphonemus gouramy Lacepede ) with a concentration of 250 ppm-3250 ppm with a diameter of the inhibition zone ranging from 6.5-11.5 mm. The most effective solvent to extract antimicrobial compounds from the bark of Saccoglottis gabonensis is methanol; Rastina, 2015; Rahmawati & Bintari, 2014, extracting methanol from the bark of the bay plant with a concentration of 80% has the ability to inhibit the growth of Escherchia coli bacteria followed by ethanol from Bligo Fruit extract (B. hispida Thunb) which has good inhibitory power at a concentration of 10% against Staphylococcus typhimurium bacteria. 70% ethanol. Among the various types of solvents, ethanol and methanol solvents are most often used for the extraction of antibacterial compounds from plant materials.